Time Sensitive Network and Its Application Exploration in Rail Transit Field - DONG Heng; WANG Chan (Kongzhi Yu Xinxi Jishu)
Time sensitive network (TSN) is considered as the evolution tendency of the next network generation, and the application of TSN technology is discussed in this paper. Firstly, relevant technical standard protocols are introduced, advantages of TSN are analyzed, and the strategic planning and development of TSN technology among domestic and foreign relevant manufacturers are investigated. Then, the application status of TSN in relevant industries is analyzed. Combined with the characteristics of TSN and the actual situation of communication system in the field of rail transit, an idea of applying TSN to the data communication subsystem of rail transit is put forward, and the specific network architecture is conceived to prove that the TSN can realize the deterministic transmission of multiple services in the same network. Finally, problems faced by wide application of TSN technology are analyzed.